2015
DOI: 10.1007/s00216-015-8719-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 18 urinary mercapturic acids by two high-throughput multiplex-LC-MS/MS methods

Abstract: Mercapturic acids (MAs) are metabolic end products formed from conjugates between glutathione and electrophilic compounds. MAs are, therefore, suitable biomarkers of exposure to toxicants, which are either electrophiles by themselves or metabolized to electrophilic intermediates. We developed and validated two LC-MS/MS methods which allow the complementary, rapid, and sensitive determination of MAs derived from acrolein, acrylamide, acrylonitrile, benzene, 1,3-butadiene, crotonaldehyde, N,N-dimethylformamide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
49
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 34 publications
28
49
3
1
Order By: Relevance
“…The levels of mercapturic acids found in the present study were largely comparable with those previously reported for non-smokers of the general population; differences were noted only for HMPMA and SBMA, with control subjects of this study showing higher levels for HMPMA and lower levels for SBMA than in previous works [44][45][46].…”
Section: Discussionsupporting
confidence: 90%
“…The levels of mercapturic acids found in the present study were largely comparable with those previously reported for non-smokers of the general population; differences were noted only for HMPMA and SBMA, with control subjects of this study showing higher levels for HMPMA and lower levels for SBMA than in previous works [44][45][46].…”
Section: Discussionsupporting
confidence: 90%
“…Application of UHPLC specifically to bioanalysis has been reviewed (Varma et al, 2010). UHPLC analysis of structurally similar mercapturates found in the urine of smokers (Wu et al, 2012, Pluym et al, 2015) and multiple mercapturates in workers exposed to multiple volatile organic chemicals (Alwis et al, 2012) will be considered in later sections of this review.…”
Section: Liquid Chromatographymentioning
confidence: 99%
“…Simultaneous determination analysis is well suited to investigate complex exposures to volatile organic compounds (VOC) in occupational settings, in exposure of urban populations to air pollutants, and in cigarette smoke (Schettgen et al, 2008b; Ding et al, 2009; Scherer et al, 2010; Eckert & Goen, 2014; Zhang et al, 2014; Chiang et al, 2015; Li et al, 2015b; Pluym et al, 2015). Sabatini developed a simultaneous determination for the mercapturates of benzene, toluene and xylene (BTX) using FDA validation guidelines (US Department of Health and Human Services Food and Drug Administration, May 2001) to measure BTX co-exposure in traffic warden exposures to automobile exhaust and urban air pollutants examining the urine of men and women, including smokers and non-smokers (Sabatini et al, 2008, Table 3).…”
Section: Urban Air Pollutantsmentioning
confidence: 99%
“…Die CVR fĂŒr LU-und PU-Test-Proben lagen bei 9,1-31,9% (Mittelwert: 18,8%) bzw. 13,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27],0% (Mittelwert: 18,5%) und wiesen auf eine begrenzte Reproduzierbarkeit in der Analyse von 3-HPMA bei beiden Probentypen hin. Die Neuberechnung der PU-Ergebnisse unter Anwendung einer eingebettenen Kalibrierung, die aus den berichteten Peak-Bereichen fĂŒr die LU-Testproben abgeleitet war, fĂŒhrte zu einer gewissen Verbesserung der CV R -Werte (Bereich: 9,6-28,8%, Mittelwert: 16,7% The measurement of suitable biomarkers of exposure and effect is central to the evaluation of these products in humans.…”
unclassified
“…The mercapturic acid is formed by reaction of acrolein with glutathione (either spontaneously or enzymatically catalyzed by a glutathione transferase) and subsequent degradation of the tripeptide, followed by N-acetylation of the cysteine residue and reduction of the aldehyde group ( Figure 1). Liquid chromatography with tandem mass spectrometry (LC-MS/MS) is the most frequently used methodology for 3-HPMA determination in urine (11)(12)(13)(14)(15)(16)(17). In a series of studies, urinary 3-HPMA levels were analyzed in smokers and non-smokers, showing, on average, about 5-fold higher levels in smokers (12,13,16,(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%